2003
DOI: 10.1101/lm.64503
|View full text |Cite
|
Sign up to set email alerts
|

Recognition Memory for Complex Visual Discriminations Is Influenced by Stimulus Interference in Rodents With Perirhinal Cortex Damage

Abstract: Rats with perirhinal cortex (PRC), hippocampal, or sham lesions were trained on a successive discrimination go/ no-go task to examine recognition memory for an array of visual objects with varying interference among the objects in the array. Rats were trained to recognize a target array consisting of four particular objects that could be presented in any one of four possible configurations to cover baited food wells. If the four target objects were presented, the rat should displace each object to receive food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 41 publications
5
34
0
Order By: Relevance
“…Although accuracy was slightly lower in rats with hippocampal lesions, compared to controls, the learning of the groups was not statistically different. In contrast, rats with perirhinal cortex lesions were significantly impaired in utilizing a pattern separation function compared to both control and hippocampal-lesioned rats (Gilbert & Kesner, 2003). The results suggest that temporal pattern separation for objects is affected by stimulus interference in rodents and is mediated by the perirhinal cortex.…”
Section: Pattern Separation --Sensory-perceptual Attribute (Objects)mentioning
confidence: 66%
“…Although accuracy was slightly lower in rats with hippocampal lesions, compared to controls, the learning of the groups was not statistically different. In contrast, rats with perirhinal cortex lesions were significantly impaired in utilizing a pattern separation function compared to both control and hippocampal-lesioned rats (Gilbert & Kesner, 2003). The results suggest that temporal pattern separation for objects is affected by stimulus interference in rodents and is mediated by the perirhinal cortex.…”
Section: Pattern Separation --Sensory-perceptual Attribute (Objects)mentioning
confidence: 66%
“…27 In our study, we used two behavioral tests of memory, a contextual fear conditioning test and NORT, to evaluate the effect of chronic hyponatremia on memory more definitively. The contextual fear conditioning test evaluates associative memory and NORT evaluates recognition memory, and they are mainly dependent on the hippocampus 34 and perirhinal cortex, [35][36][37] respectively. Therefore, it is suggested that chronic hyponatremia affects several kinds of memory and a broad range of brain areas related to memory processing.…”
Section: Discussionmentioning
confidence: 99%
“…Previous controls for difficulty in complex visual discriminations (Bussey et al, , 2003Gilbert and Kesner, 2003), oddity tasks (Buckley et al, 2001), and object recognition (Norman and Eacott, 2004) have used size, colors, shapes, or numbers of stimuli as a control for difficulty and have consistently revealed that simply increasing the difficulty of a task is not sufficient to produce PRh Oddity Preference Score Figure 8. Spontaneous oddity preference performance by control, PPRh, and PRh groups in experiment 4.…”
Section: Discussionmentioning
confidence: 99%